Cardiac involvement in total generalized lipodystrophy (Berardinelli- Seip syndrome) - Viégas,Ruy Felipe Melo (2000)
Total generalized lipodystrophy (Berardinelli--Seip Syndrome) is a rare hereditary disease characterized by insulin-resistant diabetes mellitus and a small quantity of adipose tissue and is of unknown origin. Common cardiovascular alterations related to this syndrome are cardiac hypertrophy and arterial hypertension. This article reports a case of Berardinelli--Seip syndrome and reviews the literature with special emphasis on the cardiovascular manifestations of this syndrome.